Can patients with oral allergy syndrome be at risk of anaphylaxis?. Issue 5 (October 2020) - Skypala, Isabel J.
Abstract : Purpose of review: Oral allergy syndrome, also known as pollen-food syndrome (PFS), is a condition usually associated with adults and characterized by mild transient oropharyngeal symptoms. The purpose of this review is to determine whether systemic or anaphylactic reactions do occur and if so, who is affected and what are the triggers. Recent findings: An increasing number of studies demonstrate that PFS occurs all age groups, and a significant number of affected adults do experience systemic and anaphylactic reactions. The upsurge in the adoption of vegan lifestyles, increase in consumption of fruits and vegetables including smoothies and juices, and use of plant foods in nutritional or body-building supplements, could exacerbate this. Changes in pollen and pollution levels, cofactors and sensitization to other plant food allergens may also be involved. Summary: While the majority of those with PFS will continue to experience mild symptoms, all individuals should be properly advised regarding the dangers of concentrated or unusual forms of plant food allergens such as smoothies, juices, soy/nut milks and nutritional supplements. Further well characterized studies are needed to determine risk factors for severe reactions, and sensitization patterns to pollens and plant food allergens.